(untitled) (Swiss Medical Weekly, 2015)
Echoing the “less is more” and “choosing wisely” campaigns in the USA, the “smarter medicine” campaign launched in 2014 by the Swiss Society of General Internal Medicine listed five tests or treatments that are often prescribed in ambulatory general internal medicine, but that may not provide any meaningful benefit and may carry the risk of generating harms and costs. In the United Kingdom, the National Institute for Health and Care Excellence (NICE) supported the National Health Services in identifying “low value” activities that should be stopped. Political pressure and stringent regulatory measures for pharmaceuticals and medical technology triggered major controversy and opposition. NICE efforts now concentrate on editing guidelines based on consensus techniques, which integrate the evidence from systematic reviews with social values and patient preferences. To obtain significant changes and promote the paradigm of reducing unnecessary waste of medical resources, opinion leaders and leading scientific or academic institutions, as well as medical societies, can make a difference, together with consumer associations and the lay press. Politicians can undoubtedly contribute to the success of these strategies, but rather than putting physicians alone under pressure and setting up stringent regulatory measures, they should network with all stakeholders and put emphasis on a broader agenda, the one of improving healthcare quality and efficiency.